Principales alteraciones bucales identificadas en pacientes geriátricos portadores de prótesis total en el centro de día para la tercera edad ¨vida a los años¨ - Eugenio Álvarez, Kerly Dayana (2025)
Introduction: The older adult population, corresponds those patients who should occupy a priority attention in relation to oral health, due to the prevalence factor such as age, these patients in a large percentage use total prostheses the same that without proper control, dental care can generate serious injuries among them; Fissured epulis, leukoplakia, angular cheilitis, candidiasis, oral pseudomembranous and gastric diseases caused by poor swallowing of food, as well as the chronological loss of soft and hard tissues caused by the lack of asepsis and prosthetic adaptation. Objective: To determine the main oral alterations that occur in older adults with total prostheses at the ¨life to the years¨ day centre for the elderly. Methodology: A descriptive cross-sectional methodology was used, and the population of 38 geriatric adults over 60 years of age who use total prostheses was identified. Results: Oral lesions were present in 92.1% of the older adults. Subprosthetic stomatitis (36.84%) was the most prevalent oral alteration, significantly affecting the palatal region. The existence of lesions was most prevalent in those individuals whose prosthetic appliances had been in use for more than 10 years and were in a poor condition. According to health status, 15.79% geriatricians suffer from diabetes and heart disease which presented subprosthetic stomatitis. Conclusions: It was evidenced that older adults at the center suffer from systemic diseases that are related to the appearance of subprosthetic stomatitis, leukoplakia and fissured epulis when associated with inadequate control, change of total prosthesis and as age advances.